Effects of Hydroxypropyl Methylcellulose and Xanthan Gum Concentrations on Virgin Coconut Oil Emulsion and Construction of Template Oleogel - Zongbo JIANG; Jun XU; Fen SHI; Qiuyang LIANG; Xing CHEN; Xinpeng BAI (Shipin gongye ke-ji, 2022)
In this study, virgin coconut oil gels with different hydroxypropyl methylcellulose (HPMC) and xanthan gum (XG) concentrations were prepared by the emulsion template method. The particle size distribution, microstructure observation, rheological behavior, oil retention and crystallinity were used to investigate the influence of HPMC and XG concentration on the formation and physical properties of virgin coconut oil emulsion and oleogel. The particle size analysis and microstructure results showed that high-concentration HPMC had better emulsification performance, and a stable emulsion with smaller oil droplet size was obtained. The change of XG concentration had no significant effect on the oil droplet size. The rheological results showed that the mechanical strength of emulsions and oleogels increased with the increase of HPMC or XG concentration, and all oleogels showed a time-dependent and structural recovery. The oil loss results showed that the increase in HPMC concentration had a particularly significant impact on the oleogel oil loss, the change range was reduced from 19.6% to 3.6%. The increase in XG concentration also reduced the oil loss from 9.62% to 4.4%. However, the change of HPMC and XG concentration had no significant effect on the XRD pattern of oleogels. This study provides a theoretical basis for the construction of virgin coconut oil gel, and also provides a reference for its practical application.